An in Vitro Assay of hERG K+ Channel Potency for a New EGFR Inhibitor FHND004 - Jin, Tao; Hu, Bingxue; Chen, Shanshan; Wang, Qiang; Dong, Xue; Zhang, Yin; Zhu, Yongqiang; Zhang, Zhao (Frontiers in Pharmacology, 2018)
FHND004 is a newly synthesized epidermal growth factor receptor (EGFR) inhibitor for the treatment of non-small cell lung cancer (NSCLC). The aim of present study was to investigate the impacts of FHND004 on Human ether-à-go-go-related gene (hERG) K+ channels and the molecular mechanisms underlying of its action. Whole-cell patch clamp recording was performed on wild type (WT), mutant hERG channels heterologously expressed in HEK 293 cells or IKr endogenously expressed in HL-1 cells, respectively. FHND004 inhibited hERG K+ currents in a concentration-dependent manner with IC50 values of 8.46±0.33μM in HEK293 cells and 7.21±0.45μM in HL-1 cells, respectively. However, the inhibitory potency of FHND004 on hERG channels was significantly less than its precursor AZD9291. FHND004-induced inhibition was state-dependent with a preference within open state, but did not alter other kinetics including activation, inactivation, recovery from inactivation or deactivation. In addition, FHND004 exhibited more potent inhibitory effects onWT/A422T and WT/H562P-hERG, two known long QT syndrome (LQTS) associated KCNH2 mutations, than WT alone. Mutations of the residues at pore regions (F656C, Y652A , S624A and F557L) in hERG channels attenuated block effects of FHND004. Taken together, our results demonstrate the evidence that FHND004 is a less potent hERG blocker than its precursor AZD9291. There is, however, a need for caution in the potential use of FHND004 for treating NSCLC patients, especially in those with other concurrent triggering factors.